DIGITAL MANAGEMENT MODEL IN TOURISM VILLAGE IN INDONESIA - Indra Hastuti; Sopingi Sopingi; Ilham Hendra Prabowo; Nagasa Waka Aji (LPPM Universitas Duta Bangsa Surakarta, 2022)
The research was carried out to obtain a model for developing a tourist village based on digital management, starting with marketing a tourist village to the public through e-marketing, ordering e-tickets and reporting on sales of Tourism Village tickets. This study uses a qualitative method with a simulation observation research strategy. Observations were made in the Sidowayah Tourism Village, Klaten Regency in Umbul Siblarak, Dolanan and Tobing Villages. From the results of the preliminary survey, the condition of the Sidowayah tourist village currently has visitors, but there are still few and are local tourists. This research was conducted for 4 months divided into 2 stages. The first stage of the research is to identify and map tourism areas owned by the Sidowayah Tourism Village, this stage is carried out using a qualitative descriptive method. The second stage is to build a tourism village development model based on digital management based on the tourism sector, with the stages of making digital marketing applications, e-tickets, e-reports, application testing and application implementation in tourism village management. The results of the research are the mapping of the tourism sector and the application of the tourist village information system based on digital management. From these results, it is expected to be able to solve problems in the development of Tourism Villages, including tourist villages that are easily known to the public on a national and international scale, people who are going on vacation can choose tourist attractions and order tickets through the application and tour managers can find out the results of ticket sales at any time and make the Village Tourism is growing rapidly